2022
DOI: 10.1186/s12951-022-01420-x
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles protect rice against biotic and abiotic stresses

Abstract: Background By 2050, the world population will increase to 10 billion which urged global demand for food production to double. Plant disease and land drought will make the situation more dire, and safer and environment-friendly materials are thus considered as a new countermeasure. The rice blast fungus, Magnaporthe oryzae, causes one of the most destructive diseases of cultivated rice worldwide that seriously threatens rice production. Unfortunately, traditional breeding nor chemical approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 78 publications
2
37
0
Order By: Relevance
“…Si has been proven to play a favorable role in plant growth, mineral nutrition, mechanical strength, and resistance to fungal diseases [ 14 , 15 ]. To investigate the effect of nanoparticles on plants, the nanoparticles are usually prepared as suspensions and sprayed onto plants or by soaking the plants into suspension [ 7 , 16 , 17 ]. In this study, a SiNP200 suspension was prepared and sprayed onto the leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si has been proven to play a favorable role in plant growth, mineral nutrition, mechanical strength, and resistance to fungal diseases [ 14 , 15 ]. To investigate the effect of nanoparticles on plants, the nanoparticles are usually prepared as suspensions and sprayed onto plants or by soaking the plants into suspension [ 7 , 16 , 17 ]. In this study, a SiNP200 suspension was prepared and sprayed onto the leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Si fertilizer is mainly applied to the soil by adding silicon materials such as blast furnace slag, so as to improve the soil and promote plant growth [ 6 ]. In recent years, nanomaterials have been widely used in agriculture as growth stimulators, plant protection products, and nano-fertilizers [ 7 ]. Among these, silica nanoparticles (SiNPs) have gained increasing attention because of their unique properties, such as high pore volume, large surface area, low toxicity, high stability, controllable morphology, and ease of surface functionalization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in our experiments, although the effects of soil silicon were small compared to the relatively large effects of host resistance in reducing the severity of blast and bacterial blight; nevertheless, soil silicon added to the resistance, particularly against the more virulent strain of bacterial blight, and thereby improved seedling growth. Similar effects of silicon in reducing disease severity have been documented across a range of rice pathogens [8,15,21,22,32,[79][80][81][82]87].…”
Section: Silicon Improves General Rice Plant Healthmentioning
confidence: 54%
“…Our results corroborate previous studies that showed soil silicon to reduce the severity of blast diseases and bacterial blight in rice [ 21 , 32 , 76 , 77 , 78 , 79 , 80 ]. Applications of silicon nanoparticles to foliage have also been shown to effectively reduce (by 70%) blast disease in rice [ 81 ]. In our experiments, the effect of soil silicon in reducing the severity of both diseases was weak relative to the strong effects of the corresponding resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…The grass types—among them wheat, rye, oat, rice, and others—grow smaller and are more susceptible to diseases when the accessible silica has been substantially reduced by extensive farming. BAS has been found to enhance the resistance of plants to biotic stress, e.g., diseases, such as powdery mildew and pests, such as stem boring insects ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%